A rent-seeking perspective on imperial peace - Indraneel Dasgupta (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2024)
We model a rent-seeking contest among two 'identity ideologues', differentially located along a uni-dimensional identity continuum, and a 'mercenary', who can choose any location in-between. The contest jointly awards an identity-relevant good ('religion') and an identity-irrelevant good ('money'). The mercenary values only money, the ideologues value both money and religion. The ideologues are worse off, at an increasing rate, when the winner is located farther away. We show that, under reasonable restrictions, the following hold. A decline in the mercenary's cost of contest effort reduces conflict. Both ideologues lose in success probability but gain in expected utility. Elimination of the mercenary increases conflict and makes the ideologues more successful yet worse off. Our results rationalize 'imperial peace' - long periods of stability and social peace in multi-ethnic empires and explain why the weakening and breakdown of such empires is often associated with a sharp rise in ethnic violence within their territories.
Keywords: D72; D74; 330; Rent-seeking contest; Identitarian distance; Ethnic conflict; Imperial peace; Decolonization